A Proposed Method for Reducing the Dimension of Arabic Documents - Lowai Saleh, Aledinat; Abdullah Fadzli, Syed (International Journal of Engineering and Technology, 2018)
Dimensionality reduction is an essential data preprocessing technique for large-scale and streaming data classification tasks. It can be used to improve both the efficiency and the effectiveness of documents. Traditional dimensionality reduction approaches fall into two categories: Feature Extraction and Feature Selection. Techniques in the feature extraction category are typically more effective than those in feature selection category. The representation of Arabic texts and the possibility of reducing their size result in reducing dimension among them, thus facilitating the processes and procedures that occur on them such as measurement of similarities, text classification, etc. Though several researchers have innovated many methods to solve this problem, in this paper, we introduce an effective method to represent Arabic texts with the lowest size. This method is based on the structure or form of words in Arabic, in terms of removing all prefixes and suffixes from words in the texts as well as removing the redundant and meaningless words. This methodological procedure could help in increasing the size of texts. Remove these prefixes and suffixes from words in the text aims at reducing dimension. The experimental results presented evidence that the proposed method substantially reduces the size of text representation by 42%, taking into account the origin of texts and words that reduce dimension.Â Â